PENENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING PADA KURIKULUM MERDEKA DALAM MENINGKATKAN KEMAMPUAN BELAJAR SEJARAH KELAS XI DI SMA NEGERI 2 BAUBAU - AMALUDDIN; devanti, wa (Jurnal Pendidikan Sejarah, 2024)
The problem in this research is how to apply the Discovery Learning learning model to the independent curriculum in studying history for class XI at SMA Negeri 2 Baubau. The aim of this research is to determine the application of the Discovery Learning learning model in the independent curriculum in studying history for class XI at SMA Negeri 2 Baubau. The type of research used in this research is Classroom Action Research or PTK. Time and place This research was carried out in the even semester of the 2023/2024 academic year in class XI of SMA Negeri 2 Baubau. The population in this study was 475 people (consisting of 13 study groups), the researchers chose class XI 3, totaling 36 students from SMA Negeri 2 Baubau. Research instruments are Observation Method, Demonstration Method and Documentation Method. The data analysis techniques used are data reduction, data exposure, and drawing conclusions The results of research in cycle I of student success in cycle I during learning activities were 16 students who completed with an average score of 70.00-75.00 and those who had not completed were 20 students with an average score of 55.00-65.00 in improving students' learning abilities to study the material and questions given and in cycle II during learning activities there was an increase where there were 31 students who completed with an average score 76.00-80.00 and there were 5 students who had not completed it with an average score of 60.00-65.00, increasing students' learning abilities to study the material and questions given.